ECONOMIC GROWTH AND PROSPERITY: ARABIC AND ISLAMIC STUDIES PERSPECTIVE - Busari, Kehinde Kamorudeen (Journal of Islamic Studies and Humanities, 2024)
The Islamic world has a rich history of economic thought that has evolved over centuries, and the unique perspective of Arabic and Islamic studies provides valuable insights into contemporary economic challenges. Islamic economics, rooted in the teachings of the Qur'an and Hadith, emphasizes ethical and moral principles in economic activities. Central to this perspective is the concept of "Barakah", which signifies blessings and divine favour in economic endeavours. Arabic and Islamic scholars have long argued that true prosperity can only be achieved when economic growth is accompanied by social justice and the equitable distribution of wealth. This view underscores the importance of wealth redistribution mechanisms such as Zakāt (obligatory almsgiving) and the prohibition of usury (Ribā) to ensure economic fairness. Also, Islamic finance principles have gained global recognition for their ethical framework. Concepts like Mudārabah (profit-sharing) and Mushārakah (joint venture) promote risk-sharing and discourage exploitative practices. Those principles have led to the development of Islamic banking and finance systems, which have demonstrated resilience even in times of economic crises. Moreover, Arabic and Islamic studies emphasize the role of entrepreneurship and innovation in fostering economic growth. Historically, Islamic civilization was a central part of scientific and technological advancement, contributing to prosperity in various fields. This perspective encourages investment in education, research and development as vital drives of economic progress. Furthermore, the Arabic and Islamic worldview promotes sustainable economic practices, emphasizing the stewardship of natural resources and the avoidance of wasteful consumption. This perspective aligns with contemporary global efforts to address environmental challenges and achieve sustainable development. The Arabic and Islamic studies perspective on economic growth and prosperity offers a holistic approach that prioritizes ethical considerations, equitable distribution of wealth, innovation and sustainability. It serves as a valuable source of inspiration for policy makers, economists and scholars seeking to build inclusive and ethical economic systems that benefit society as a whole. The study employs exegetical and qualitative research approaches from the Qur'an, Hadith and other relevant textbooks, journals and online materials respectively.